MEKANISME EKSEKUSI KONTEN YOUTUBE SEBAGAI JAMINAN HUTANG DI BANK - Adi, I Made Agus Artha Prasetya; Ratnawati, Elfrida (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
In the context of civil relationships such as debt and credit, property can be used as collateral for a debt, and collateralization of property must involve a security agreement to ensure legal certainty for the creditor as the holder of the property collateral in the event of debtor default. With the rapid digitalization of our times, new forms of property collateral have emerged, including YouTube content. YouTube content is intellectual property that can be legally protected by Copyright Law. Explicitly, intellectual property protected by Copyright Law can be used as the subject of a fiduciary agreement. This opens up the possibility of YouTube content being used as collateral to obtain financing from financial institutions. This research employs a normative methedology approach, drawing from primary legal sources such as legal norms, jurisprudence, and secondary legal materials related to the research, which are sourced from legal facts, doctrine, books, journals, the internet, and other references. The results of this research provide options for executing the collateral of a defaulting debtor, one of which is by executing a fiduciary arrangement based on the default.Keywords: Debt Collateral, YouTube, Execution, Bank